Sexual function between women with gestational diabetes and low risk pregnant women in third trimester of pregnancy - Ommolbanin Zare; Masoumeh Simbar; Giti Ozgoli; Adeleh Bahar; Hamid Alavi Majd (Mashhad University of Medical Sciences, 2021)
Introduction: Given the importance of sexual issues in women's lives and being affected by various factors such as pregnancy and diabetes, and the existence of limited research on sexual function in women with gestational diabetes, this study was performed with aim to compare sexual function of women with gestational diabetes and low risk pregnant women in third trimester of pregnancy. Methods: This descriptive-analytical study was performed on 300 women with gestational diabetes  low-risk pregnant women in the clinics affiliated to Mazandaran University of Medical Sciences in 2019. Demographic data were collected using researcher-made Demographic-Midwifery Questionnaire, and data related to sexual function using Female Sexual Function Index questionnaire  Data were analyzed by SPSS software (version 23) and Independent t-test, Mann Whitney, Chi-square and Multiple linear regression. P<0.05 was considered statistically significant. Results: In this study, 131 (87.3%) of women with gestational diabetes and 52 (34.67%) of low-risk pregnant women had sexual dysfunction. Gestational diabetes causes a significant decrease in sexual desire score (P< 0.001), lubrication score (p=0.006), satisfaction score (P< 0.001) and a significant increase in pain score (p=0.01). Conclusion: Most women with gestational diabetes had sexual dysfunction; gestational diabetes predicts sexual function in pregnant women. Therefore, evaluation of sexual function should be a part of the usual assessment of women with gestational diabetes.